Vermicompost Application in Crop Production and Urban Waste Management: A Review Article - Abafita, Reshid (Discoveries in Agriculture and Food Sciences, 2022)
The marvelous increase in population, industrialization, urbanization, and agricultural output results in buildup amounts of solid wastes which lead to serious problematic in the environment. The waste management and crop residues are serious problems in the world. The burning of crop residues causes environmental pollution like smog. Disposal of these wastes safely can be achieved by bio-composting and vermicomposting of farm, agro-industrial waste and urban wastes. To manage all kind of waste vermicomposting is the best technique that is economically viable, environment friendly and socially acceptable approach which converts garbage in to black gold; called vermicomposts. Vermicomposts enhances soil biodiversity by promoting the beneficial microbes which in turn enhances plant growth directly by production of plant growth-regulating enzymes and hormones and indirectly by controlling plant diseases, nematodes and other pests, thereby enhancing plant health and minimizing the yield loss. Vermicompost may be used to promote sustainable agriculture due to its distinctive biochemical, biological and physiochemical properties and also used for the safe management of agricultural, domestic, industrial and hospital wastes which may otherwise pose serious threat to life and environment. In preparation of vermicompost, organic waste products are being oxidized via the mutual activity of useful microbes and earthworm. Vermicompost is rich source of all macro and micro nutrients, i.e., Nitrogen (N), Phosphorous (P), Potassium (K), Iron (Fe), Zinc (Zn), Copper (Cu), manganese (Mg), growth promoters and regulators hormones like Auxin, gibberellin, enzymes i.e., protease, lipase, chitinase, beneficial bacteria and fungi. Almost 3,000 species of earthworms are identified for vermicomposting, in which Eisenia fetida, Eisenia Andrei, Eudrilus eugeniae and Perionyn excavates are most suitable for vermicompost preparation. This review focuses on relevant research performed and success in using vermicomposts during the last decade that can help us improve sustainable crop production and municipals and household waste disposal.